Psychometric evaluation and clustering of the Chinese Community Integration Questionnaire-Revised (CIQ-R) among older adults: a cross-sectional study - Wang, Yuanfang; Qin, Xinglan; Xu, Lei; Zheng, Lisha; Xie, Xiaohui; Wang, Jia; Zhou, Wansha; Wang, Lianhong (Frontiers in Public Health, 2026)
BackgroundReliable instruments for assessing community integration among older adults are limited in China. The Community Integration Questionnaire–Revised (CIQ-R) was translated into Chinese and culturally adapted for use in this population. Its psychometric properties were evaluated, and its practical utility for classifying levels of community integration was examined.MethodsFollowing forward–backward translation and expert review, the Chinese Community Integration Questionnaire (CIQ)-R was administered to 400 community-dwelling older adults in Zunyi (April–July 2024). Item analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) assessed scale structure. Internal consistency was evaluated with Cronbach’s α. K-means clustering identified integration profiles and empirical cut-offs; cluster validity and between-group differences were examined with nonparametric tests and effect sizes.ResultsThe adapted CIQ-R consists of four subscales (Family Integration, Social Integration, Productivity, Electronic Social Networking) and 17 items, following the removal of one poorly performing item (item 2.4). Cronbach’s α for the full scale was 0.816. EFA (KMO = 0.808; Bartlett’s p < 0.001) yielded a four-factor structure accounting for 61.25% of the variance, with eigenvalues >1; CFA provided support for the proposed model CFA provided support for the proposed model (χ2 = 268.34, df = 84, p < 0.001; χ2/df = 3.19; CFI = 0.920; TLI = 0.900; RMSEA = 0.074, 90% CI: 0.064–0.084), indicating an acceptable overall model fit. K-means clustering identified three distinct and stable profiles (Low, Moderate, and High); empirical thresholds of 13.25 and 21 distinguished the groups (all pairwise comparisons p < 0.001).ConclusionThe Chinese CIQ-R demonstrates acceptable reliability and structural validity and provides a practical tool for identifying heterogeneity in community integration among older adults, with potential utility for population screening and community-based public health planning.Clinical trial registrationThis study was registered with the Chinese Clinical Trial Registry (ChiCTR2300071478).